Comorbidity of infantile cerebral palsy and benign epileptiform EEG discharges of childhood in dizygotic twins - M. B. Mironov; N. V. Chebanenko; V. G. Bychenko; Yu. V. Rubleva; S. G. Burd; T. M. Krasilshikova (Эпилепсия и пароксизмальные состояния, 2018)
The article presents a clinical case of infantile cerebral palsy combined with BEDC (with no epileptic seizures) in dizygotic twins. The case supports the hypothesis of genetic nature of the BEDC patterns. The variety of EEG characteristics and clinical courses of the disease in children with cerebral palsy and BEDC are reviewed. Correct interpretation of the EEG findings provides an accurate prognosis of seizures and cognitive functions, as well as the patient management tactics. In these patients, continuous video EEG monitoring (both awake and sleeping) is recommended for a long-time follow-up.